The Impact of Bank-Specific and Macro Economic Factors on Profitability in Small Banks - Soesetio, Yuli; Waffiudin, Waffiudin; Rudiningtyas, Dyah Arini; Siswanto, Ely (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: The objective of this study is to decide whether the profitability of small banks is shaped by bank-specific and macro economic factors including liquid ratio, loan to deposits ratio, deposit to assets ratio, capital adequacy ratio, firm size, GDP growth, and inflation.Method: The sample selected using purposive sampling technique as many as 77 units of analysis consisting of 42 banks in the BUKU 1 category and 35 banks in the BUKU 2 category registered with OJK since 2014-2019. After eliminated the outlier data, there were 413 observations as panel data. The analytical method used in this study is the regression panel fixed effect model and random effect model.Findings: The results indicate that liquidity and loan to deposit ratio positively affects small banks profitability in Indonesia. Meanwhile, size, deposit to asset ratio, capital adequacy ratio, and GDP growth negatively affects profitability. Nevertheless, inflation does not affect profitability. This study mention that small bank’s managers need to deal with and take notice to the bank operational well i.e liquidity and loan to deposit ratio.Novelty: This research investigates the outcome of bank-specific and macro economic factors on profitability in small banks period 2014-2019. The earlier research only check-out those variables solely and spotlight on distinctive samples and distinctive period. This study has implication for banking sector especially for small bank to pay more attention, strengthen, and maintain the exis- tence of their business through several ways, increasing and optimizing the level of equities owned to make assets increase and the cost of the funding structure becomes optimal.